HÜSÜN VE KUBUH NİÇİN HAKİKÎ DEĞİL DE İTİBÂRÎDİR?: SEYFEDDÎN elÂMİDÎ ÖRNEĞİNDE BİR İNCELEME - (:unkn) unknown (My University, 2020)
İnsan fiillerindeki değerin kaynağı konusundaki görüş ayrılıklarından doğan hüsün-kubuh (iyilik-kötülük)meselesi, Sünnî düşünce ile Mu‘tezilî düşünce arasındaki temel tartışmalardandır. Bu makalede Eş‘arî âlimSeyfeddin el-Âmidî’nin (öl. 631/1233), fiildeki hüsün-kubuh değerlerinin zâtî olduğunu savunan Mu‘tezile’yekarşı, fiildeki bu değerlerin zâtî olmayıp itibârî olduğunu nasıl temellendirdiği konusu ele alınmıştır. Âmidîözelinde Eş‘arîler’e göre insanın, bu dünyada övgüye âhirette de sevâba ya da bu dünyada kınanmaya âhirette decezâya müstehak olacağı fiiller hasen ya da kabîh olarak adlandırılır. Buna göre insanın fiili onu dünyada övgüyeâhirette de sevaba ulaştırırsa bu fiil hasen fiil, şayet bu dünyada kınanmayı âhirette de cezâyı gerektirirse bu fiilkabîh fiil olur. Fiildeki bu değerler, sadece şeriatın belirlemesiyle oluşur. Yani insan aklı hangi fiillerin bukategoriye girdiğini bilemez. Hasen ve kabîhin doktrinde tartışma konusu olan bu anlamının yanında sahipolduğu iki anlam daha vardır. Bunlar: 1.Amaca veya tabiata uygunluk ve aykırılık; 2. Failin yapma hakkınınolması hususlarıdır. Fakat bu iki anlam hakkında tartışma yoktur.

The matter of ḥusn (goodness) and qubḥ (evil), which is the result of the disagreements on the source of moral value in human actions, is one of the main disputes between the Sunnī schools and the Muʿtazilī school of theology. This study examines the reasons why Sayf al-Dīn al-Āmidī, the Ash‘arī scholar, argues that the values of the ḥusn- qubḥ in actions are relative (i‘tibārī) against to the Mu‘tazilī school that considers these values to be inherent in actions. According to the Ash‘arīs, and specifically al-Āmidī, if the actions make people worth of either praise in this world and reward (thawāb) in afterlife or blame in this world and punishment in afterlife, those actions are named as ḥasan (good) or qabīḥ (bad). Therefore, if the action of a person provides him/her praise in this world and reward in afterlife, the action is called ḥasan. If an action necessitates condemnation in this world and punishment in the afterlife, the action is called qabīḥ. The moral values in actions can only be determined by the Sharī‘a. In other words, human reason cannot know which actions are included in the category of ḥasan and qabīḥ. In addition to their contentious meanings in the doctrine, ḥasan and qabīḥ have two more meanings. The first one is the suitability and contrariety to the purpose or disposition while the second one is the agent’s right of doing any given action. However, there is no debate about these two meanings.
WHY ḤUSN AND QUBḤ ARE NOT INHERENT BUT RELATIVE?: A STUDY IN THE EXAMPLE OF SAYF AL-DĪN AL-ĀMİDĪ